NFATc1/αA and Blimp-1 Support the Follicular and Effector Phenotype of Tregs - Koenig, Anika; Vaeth, Martin; Xiao, Yin; Chiarolla, Cristina M.; Erapaneedi, Raghu; Klein, Matthias; Dietz, Lena; Hundhausen, Nadine; Majumder, Snigdha; Schuessler, Felix; Bopp, Tobias; Klein-Hessling, Stefan; et al. (Frontiers in Immunology, 2022)
CD4+CXCR5+Foxp3+ T-follicular regulatory (TFR) cells control the germinal center responses. Like T-follicular helper cells, they express high levels of Nuclear Factor of Activated T-cells c1, predominantly its short isoform NFATc1/αA. Ablation of NFATc1 in Tregs prevents upregulation of CXCR5 and migration of TFR cells into B-cell follicles. By contrast, constitutive active NFATc1/αA defines the surface density of CXCR5, whose level determines how deep a TFR migrates into the GC and how effectively it controls antibody production. As one type of effector Treg, TFR cells express B lymphocyte-induced maturation protein-1 (Blimp-1). Blimp-1 can directly repress Cxcr5 and NFATc1/αA is necessary to overcome this Blimp-1-mediated repression. Interestingly, Blimp-1 even reinforces the recruitment of NFATc1 to Cxcr5 by protein-protein interaction and by those means cooperates with NFATc1 for Cxcr5 transactivation. On the contrary, Blimp-1 is necessary to counterbalance NFATc1/αA and preserve the Treg identity. This is because although NFATc1/αA strengthens the follicular development of Tregs, it bears the inherent risk of causing an ex-Treg phenotype.